Application Review of Comprehensive Multi-index Evaluation Methods in River Health Evaluation - YANG Xiaoyan; WANG Chi; WU Tian; XIA Tiyuan (Renmin Zhujiang)
To understand the current research progress and direction of comprehensive multi-index evaluation methods,and supplement the principle and method of evaluation index screening,this paper summarizes the research progress of the comprehensive multi-index evaluation method in river health evaluation at home and abroad.Firstly,the concept and evaluation principle of comprehensive multi-index evaluation are summarized from the perspective of river health evaluation objects and evaluation methods by tracing the domestic and foreign literature.Meanwhile,the three hierarchies of river health evaluation are illustrated by taking the target-criterion-index structure of river health evaluation in Yunnan Province as an example.Secondly,the current research progress of comprehensive multi-index evaluation methods and the index selection rationality are emphasized.Finally,the problems existing in the comprehensive multi-index evaluation methods are analyzed and the corresponding solutions are put forward.As a result,this paper provides references for river health management in China,and also scientific and technological support for the smooth promotion of river chief systems in various places.